The Kids' Empathic Development Scale (KEDS): A multi‐dimensional measure of empathy in primary school‐aged children. (2nd November 2012) - Reid, Corinne; Davis, Helen; Horlin, Chiara; Anderson, Mike; Baughman, Natalie; Campbell, Catherine
<x xml:space="preserve">Abstract</x> Empathy is an essential building block for successful interpersonal relationships. Atypical empathic development is implicated in a range of developmental psychopathologies. However, assessment of empathy in children is constrained by a lack of suitable measurement instruments. This article outlines the development of the Kids' Empathic Development Scale (KEDS) designed to assess some of the core affective, cognitive and behavioural components of empathy concurrently. The KEDS assesses responses to picture scenarios depicting a range of individual and interpersonal situations differing in social complexity. Results from 220 children indicate the KEDS measures three related but distinct aspects of empathy that are also related to existing measures of empathy and cognitive development. Scores on the KEDS show age and some gender‐related differences in the expected direction.